63.3k views
5 votes
Simplify √75a+ √12a - √27a

------------------------------
√3a
a) 1/4
B)-4
C)4

1 Answer

3 votes

Answer: OPTION C.

Explanation:

You have the expression:


(√(75a)+√(12a)-√(27a))/(√(3a))

Descompose the numbers into its prime factors:


75=3*5*5=3*5^2


12=2*2*3=2^2*3\\27=3*3*3=3^2*3

Substitute and simplify


=(√(3*5^2*a)+√(2^2*3*a)-√(3^2*3*a))/(√(3a))


=(√(3*5^2*a)+√(2^2*3*a)-√(3^2*3*a))/(√(3a))\\\\=(5√(3a)+2√(3a)-3√(3a))/(√(3a))\\\\=(4√(3a))/(√(3a))\\\\=4

User Alexandre
by
5.5k points